Intraseasonal descriptors and extremes in South African rainfall. Part I: Summer climatology and statistical characteristics. (29th December 2021) - Ullah, Asmat; Pohl, Benjamin; Pergaud, Julien; Dieppois, Bastien; Rouault, Mathieu
Abstract: Rainfall extremes are of major and increasing importance in semi‐arid countries and their variability has strong implications for water resource and climate impacts on the local societies and environment. Here, we examine intraseasonal descriptors (ISDs) and wet extremes in austral summer rainfall (November–February) over South Africa (SA). Using daily observations from 225 rain gauges and ERA5 reanalysis between 1979 and 2015, we propose a novel typology of wet extreme events based on their spatial fraction, thus differentiating large‐ and small‐scale extremes. Long‐term variability of both types of extreme rainfall events is then extensively discussed in the context of ISDs. The results demonstrate that using 7% of spatial fraction simultaneously exceeding the local threshold of the 90th percentile produces remarkable results in characterizing rainfall extremes into large‐ and small‐scale extremes. Austral summer total rainfall is found to be primarily shaped by large‐scale extremes which constitute more than half of the rainfall amount under observation, and nearly half in ERA5. Observation (ERA5) shows an average of 8 ± 5 (20 ± 7) days per season associated with large‐scale extremes, which are comprised in 5 ± 3 (10 ± 3) spells with an average persistence of at least 2 days. Overall, we find a strong dependence of total rainfall on the number of wet days and wet spells that are associated with large‐scale extremes. We also find that large‐ and small‐scale extremes are well‐organized and spatially coherent in nature yet extreme conditions during small‐scale events are found sporadic over the region, contrasting with large‐scale events for which extreme conditions are found over a larger and coherent region. Abstract : This study addresses the intraseasonal descriptors (ISDs) and wet extremes in austral summer rainfall (November–February) over South Africa (SA). We propose a novel typology of wet extreme events based on their spatial fraction, thus differentiating large‐ and small‐scale extremes. The attention is then given to the spatial characteristics and coherence of rainfall extremes. Long‐term variability of both types of extreme rainfall events is also provided in the context of ISDs. Our results show that austral summer total rainfall is primarily shaped by large‐scale extremes which constitute more than half of the rainfall amount under observation, and nearly half in ERA5. Overall, we find a strong dependence of total rainfall on the number of wet days and wet spells that are associated with large‐scale extremes. We also find that large‐ and small‐scale extremes are well‐organized and spatially coherent in nature yet extreme conditions during small‐scale events are found sporadic over the region, contrasting with large‐scale events for which extreme conditions are found over a larger and coherent region.